Dinamika Kawasan Pasifik Barat Daya Dalam Percaturan Global - Burhanuddin, Burhanuddin (FISIP UNHAS, 2015)
Abstrak : Kawasan Pasifik Barat Daya dalam percaturan Politik Global mengacu pada dua tujuan yakni mengetahui kepentingan Negara-negara besar di Kawasan Pasifik Barat Daya dan mengetahui kepentingan Negara-negara besar di Kawasan Pasifik Barat Daya.Metode yang digunakan dalam penelitian ini adalah metode Deskriptif-Analitif yang memberikan gambaran mengenai fenomena-fenomena yang terjadi dan relevan.dan menggambarkan kawasan Pasifik Barat Daya dan nilai strategisnya serta interaksinya,dengan fihak Internasional. Dan dari data ini kemudian menganalisa kepentingan Negara-negara besar dan perebutan pengaruh yang terjadi di antara mereka. Dari hasil penelitian menunjukkan bahwa kawasan pasifik barat daya terdiri dari 22 unit politik yang juga dikenal dengan nama Pasifik Selatan atau Oceania,nilai strategis dan sejumlah kepentingan Internasional hadir di region ini. Beberapa Negara besar yang berkepentingan dan menanamkan pengaruhnya di kawasan tersebut, misalnya Australia dan New Zealand, Amerika Serikat, perancis, China dan Jepang kehadiran Australia dan New Zealand tidak lepas dari kedekatan dan statusnya sebagai bagian dari kawasan ini. Kata kunci : Kawasan Pasifik Barat Daya, Politik Global, Negara Negara BesarAbstract : This study aimed to determine the Southwest Pacific Region in the political arena. This research was conducted with reference to the two objectives, namely: to know the interests of the big countries in the Southwest Pacific Region and to determine the seizure of the interests of the big countries in the region.The method used in this research is descriptive analytical method is to provide a picture of the phenomenon relevant to the problems studied and analyzed to answer the problem. Through this method, the authors describe the Southwest Pacific region and its strategic value and its interaction with international parties. By having this data then analyzed the interests of the big countries and the struggle for influence that happened between them. As for the data collection techniques which used is by reviewing the literature (library research), by collecting data from the literature related to the discourse discussed. The results of this study indicate that the Southwest Pacific region comprises 22 political units which are also known as the South Pacific or Oceania. Departing from a number of strategic values, a number of international interests is present in this region. Some big countries which concerned and attempts to influence over this region there are Australia, New Zealand, United States, France, China and Japan. The presence of Australia and New Zealand can not be separated from its proximity and status as part of this region.Key words : Southwest Pacific Region, Global political